Big gorilla : a book of opposites - Browne, Anthony, 1946- (Candlewick Press, 2024)
What's the opposite of old? Young! What's the opposite of sad? Happy! But what's the opposite of opposite...? Featuring a range of exquisite primates, from gorillas to chimpanzees, white-faced capuchins to orangutans, Anthony Browne has created a wonderfully unique first book of opposites, with his striking palette and quirky flair for facial expressions sure to charm readers of all ages.